Epidemiological investigation on canine babesiosis in Tarai region of Uttarakhand - KUNWAR, VIDHI; BHATT, PRAKASH; KUMAR, SATISH; YADAV, MRIGAKSHI; SINGH, A K (The Indian Journal of Animal Sciences, 2021)
Babesiosis is a haemoprotozoan disease caused by hemotropic protozoa of the Babesia genus. It is an emerging disease and has zoonotic importance which continues to emerge worldwide. It has significant economic impact on livestock and pet animals; especially in the tropical and subtropical regions. The present study was undertaken in different epidemiological aspect on canine babesiosis in Tarai region of Uttarakhand. The overall prevalence of canine babesiosis was recorded as 23.63% based on retrospective study; out of which 55.44% dogs were infested with ticks on hospital records. It was more prevalent in males (25.89%) as compared to female dogs (19.74%). The maximum prevalence was seen in German Shepherd (29.03%) as compared to Bull Mastiff (5.25%). Young dogs (1-3 years of age) were comparatively more affected in comparison to adult dogs. The highest prevalence was found in July (33.33%) whereas least was recorded in December (8.04%). High rise of temperature, tick infestation, anorexia, dehydration, lethargy, etc. were the characteristic clinical signs of canine babesiosis.